Teaching English to Learners with Dyslexia: Challenges, Strategies and Implications - Brahim Mrissa (Journal of Research in Education and Pedagogy, 2026)
This paper explores the challenges and prospects of teaching English to learners with dyslexic brains, with particular attention to how dyslexia influences language acquisition and classroom performance. Dyslexia poses specific difficulties in reading, spelling, and phonological processing, which can hinder progress in English as a foreign language if not appropriately addressed. The study aims to inform teachers and educational practitioners about effective, inclusive teaching practices that can be tailored to the needs of dyslexic learners, and provide insights for textbook designers and curriculum developers to consider learning difficulties when designing English language materials. To achieve these objectives, the study adopts a quantitative research approach. A structured questionnaire was administered to English language teachers to investigate their experiences, perceptions, and classroom practices when teaching students with dyslexia. The findings reveal that multisensory instructional techniques, differentiated instruction, and individualized support strategies significantly enhance learner engagement and language outcomes. Additionally, results indicate that teachers’ professional experience and prior training in learning difficulties strongly influence their confidence and perceived effectiveness when working with dyslexic students. Despite these positive practices, challenges persist, including large class sizes, limited resources, insufficient training opportunities, and the continued stigma surrounding learning difficulties. These obstacles often prevent teachers from fully meeting the individual needs of dyslexic learners. Overall, the study highlights the critical role of teacher training, inclusive classroom adaptations, and informed material design in supporting dyslexic students. The findings offer practical implications for educators, school administrators, and textbook designers, emphasizing the need for collaborative efforts to create more inclusive and accessible English language learning environments.